SELF-CONFIDENCE ON ACQUIRED SURGICAL SKILLS TO DEAL WITH SEVERE TRAUMA PATIENTS IN RECENTLY GRADUATED SURGEONS - VELA,Javier (2021)
ABSTRACT Background: Trauma is one of the leading causes of death in the world and proper surgical care is critical to impact mortality. In Chile, trauma associated death ranks first as mortality cause in population between 20 and 59 years old. Appropriate surgical skills are required to deal with these complex patients. Self-confidence to practice trauma procedures after the General Surgery Residency have not been reported in our country. Aim: Describe the level of self-confidence to deal with trauma procedures of surgeons who recently graduated from a General Surgery Residency. Method: Descriptive cross-sectional study. We designed and applied a survey in 2015, 2016 and 2017 to recently graduated surgeons, to inquire about self-confidence of surgical skills to deal with trauma scenarios. Eighteen trauma surgery procedures (including cervical, thoracic, abdominal and vascular procedures) were evaluated using a 5-grade Likert scale. The number of procedures performed during the residency was also queried. Results: Eighty-eight recently graduated surgeons from 11 different training programs in Chile were included. The report of competencies was high in procedures such as intestinal injuries, were 98% felt competent or very competent in their repair. On the other hand, in complex traumas such as major vessel injury, up to 76% reported not being competent. Self-confidence on procedures was directly associated with the number of procedures performed during residency. Conclusions: Recently graduated surgeons from General Surgery Programs report high levels of confidence to deal with low and intermediate complexity traumas, but a lower level of confidence to treat high complexity cases.